The Mucin-like Macroglycopeptide Region of Glycoprotein Ibα is Required for Cell Adhesion to Immobilized von Willebrand Factor (VWF) Under Flow but not for Static VWF Binding - Li, Chester Q.; Dong, Jing-fei; López, José A. (Thrombosis and Haemostasis, 2002)
A dominant feature of the structure of platelet glycoprotein (GP) Ibα, the von Willebrand factor (VWF)-binding subunit to the GP IbIX-V complex, is the presence of an elongated, heavily glycosylated mucin-like stalk between the plasma membrane and the N-terminal 45-kDa ligand-binding domain. Here, we investigated the function of that region by expressing a mutant lacking residues 318-452 as part of a recombinant GP Ib-IX complex. We studied the VWF-binding function of this mutant under both static conditions and flow. The mutant GP Ibα was expressed normally on the surface of CHO bIX cells (stably expressing GP Ibβ and GP IX) and the proper conformation of the ligand-binding region was verified by the normal binding of 5 conformation-sensitive monoclonal antibodies. Under static conditions, cells expressing mutant GP Ibα bound VWF (binding induced by either botrocetin or ristocetin) in a manner indistinguishable from cells expressing wild-type GP Ibα. We also evaluated the ability of the mutant to mediate cell adhesion to immobilized VWF in the presence of fluid shear stress (at 2 and 10 dyn/cm2). When the mutant-expressing cells were incubated with immobilized VWF for 1 min before being exposed to shear, they rolled on the VWF surface in a manner similar to wild-type cells. However, if the cells were not first allowed to settle on the surface before the application of shear stress, the mutant GP Ibα was unable to capture the cells onto the VWF surface from the fluid stream, an indication that steric hindrance from other cell surface molecules may prevent access of the GP Ibα ligand-binding site to the surfaceimmobilized VWF.
Keywords: Platelet adhesion; glycoprotein Ib; von Willebrand factor; macroglycopeptide